Metabolic Targets of Coenzyme Q10 in Mitochondria - Agustín Hidalgo-Gutiérrez; Pilar González-García; María Elena Díaz-Casado; Eliana Barriocanal-Casado; Sergio López-Herrador; Catarina M. Quinzii; Luis C. López (MDPI AG, 2021)
Coenzyme Q10 (CoQ10) is classically viewed as an important endogenous antioxidant and key component of the mitochondrial respiratory chain. For this second function, CoQ molecules seem to be dynamically segmented in a pool attached and engulfed by the super-complexes I + III, and a free pool available for complex II or any other mitochondrial enzyme that uses CoQ as a cofactor. This CoQ-free pool is, therefore, used by enzymes that link the mitochondrial respiratory chain to other pathways, such as the pyrimidine de novo biosynthesis, fatty acid β-oxidation and amino acid catabolism, glycine metabolism, proline, glyoxylate and arginine metabolism, and sulfide oxidation metabolism. Some of these mitochondrial pathways are also connected to metabolic pathways in other compartments of the cell and, consequently, CoQ could indirectly modulate metabolic pathways located outside the mitochondria. Thus, we review the most relevant findings in all these metabolic functions of CoQ and their relations with the pathomechanisms of some metabolic diseases, highlighting some future perspectives and potential therapeutic implications.